Study of protectivity and antigenicity of vaccine based on ' cultural Asia-1 No.2145/ Tajikistan/2011 FMD Virus - D. A. Lozovoy; V. A. Starikov; D. V. Mikhalishin (Ветеринария сегодня)
The paper presents the results of tests aimed to study the protective antigen differences between Asia-1 No. 2145/Tajikistan/2011 isolate and Asia-1 Shamir 3/89 FMD cultural virus vaccine strain.